Autophagy as an emerging arena for plant–pathogen interactions. (August 2017) - Hofius, Daniel; Li, Liang; Hafrén, Anders; Coll, Nuria S
Highlights: Autophagy is an integral part of plant–pathogen interactions. A large variety of microbial pathogens target or are targeted by plant autophagy. Autophagy in eukaryotic microbial pathogens is essential for pathogenesis. Plant autophagy participates in defense responses against invading microbes. Successful pathogens have evolved strategies to manipulate plant autophagy. Abstract : Autophagy is a highly conserved degradation and recycling process that controls cellular homeostasis, stress adaptation, and programmed cell death in eukaryotes. Emerging evidence indicates that autophagy is a key regulator of plant innate immunity and contributes with both pro-death and pro-survival functions to antimicrobial defences, depending on the pathogenic lifestyle. In turn, several pathogens have co-opted and evolved strategies to manipulate host autophagy pathways to the benefit of infection, while some eukaryotic microbes require their own autophagy machinery for successful pathogenesis. In this review, we present and discuss recent advances that exemplify the important role of pro- and antimicrobial autophagy in plant–pathogen interactions.